Manufacturing engineering : selected, peer reviewed papers from the 1st International Manufacturing Engineering Conference (iMEC 2013), July 1-3, 2013, Gambang, Kuantan, Pahang, Malaysia - Yusoff, Ahmad Razlan; Iskandar, Ismed (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 1st International Manufacturing Engineering Conference (iMEC 2013), July 1-3, 2013, Gambang, Kuantan, Pahang, Malaysia. The 75 papers are grouped as follows: Chapter 1: Materials and Manufacturing Process, Chapter 2: Engineering, Manufacturing Automation and Optimization, Chapter 3: Manufacturing Systems and Management Keyword: Materials and Manufacturing Process, Engineering, Manufacturing Automation and Optimization, Manufacturing Systems and Management.